POST-COVID CONDITION - PULMONARY OR SYSTEMIC, REVERSIBLE OR IRREVERSIBLE? - Škodrić Trifunović, Vesna (Medicinski podmladak, 2023)
Covid patients are being discharged from hospitals without assessment of the degree of their recovery. Large number of patients fully recovers after covid. However, over 30% of patients have prolonged symptoms, independent from the severity of their clinical picture. There is no correlation between severe acute COVID and severe post-COVID syndrome. According to the NICE 2020 recommendations, the term long covid includes symptomatic COVID-19 (period 4-12 weeks after acute disease) and post- COVID-19 syndrome. According to the WHO post-COVID-19 syndrome is a condition in persons with history of probable or confirmed COVID infection, usually 3 months from the onset of COVID-19, with symptoms lasting at least 2 months, that cannot be explained by an alternative diagnosis. Intolerance to physical exertion, experiencing breathing difficulty and neuropsychiatric disorders are the most common and longest lasting difficulties. Most common respiratory post-COVID manifestation is persistent dyspnea, while persistent pulmonary fibrosis was extremely rare. In almost half of patients who have had severe COVID pneumonias, there were no absolute correlation between pulmonary function disorders and thoracic CT images, and disorders kept persisting after complete radiographic regression. Dominant manifestation of these disorders is reduced lung diffusion capacity for CO (TLCOc, KCOc), while spirometry values are mostly normal. Pulmonary thromboembolism, myocarditis, anxiety-depressive disorder, forgetfulness and hair loss are some of the serious post-COVID complications. Significant number of patients need physical rehabilitation.
Keywords: postcovid; recovery; pulmonary function; pulmonary fibrosis